Life history traits and functional processes generate multiple pathways to ecological stability - John P. DeLong; Torrance C. Hanley; Jean P. Gibert; Linda M. Puth; David M. Post (Ecology, 2018)
Stability contributes to the persistence of ecological communities, yet the interactions among different stabilizing forces are poorly understood. We assembled mesocosms with an algal resource and one to eight different clones of the consumer Daphnia ambigua and tracked algal and Daphnia abundances through time. We then fitted coupled ordinary differential equations ( ODE s) to the consumer–resource time series. We show that variation in different components of stability (local stability and the magnitude of population fluctuations) across mesocosms arises through variation in life history traits and the functional processes represented by ODE model parameters. Local stability was enhanced by increased algal growth rate and Daphnia mortality and foraging rate. Population fluctuations were dampened by high Daphnia conversion efficiency and lower interaction strengths, low algal growth rate, high Daphnia death rate, and low Daphnia foraging. These results indicate that (1) stability in consumer–resource systems may arise through the net effect of multiple related stabilizing pathways and (2) different aspects of stability can vary independently and may respond in opposite directions to the same forces.